Fluctuating Dental Arch Asymmetry in Different Malocclusion Groups - Ana Škrinjarić (Acta Stomatologica Croatica, 2018)
Objective: To compare the degree of dental arch fluctuating asymmetry (FA) among patients with Class I, II, and III malocclusions. Subjects and methods: The sample comprised randomly selected plaster casts of 131 patients: 39 Class I (19 males and 20 females), 57 Class II (23 males and 34 females), and 35 Class III (20 males and 15 females). Dental models were scanned and digitized using ATOS II SO. The measurements of the teeth and dental arches were taken using the ATOS viewer version 6.A.2 software. Six arch widths and five arch depths were measured. The FA was assessed as a composite index of total weighted asymmetry (TWA). The analysis of variance was used to determine whether there were any statistically significant differences between the groups. Results: Composite TWA measures of fluctuating asymmetry for dental arch variables were the highest in Class III, and lowest in Class I malocclusion. Males displayed a higher degree of asymmetry than females. The asymmetry degree was higher in the mandibular dental arches than in the maxillary dental arches in all malocclusion groups. Conclusion: The TWA values were low but they differed significantly between the groups of malocclusion. Class III malocclusion displayed higher FA values than Class I and Class II malocclusion. Higher FA of dental arches in Angle’s Class III can be considered an indicator of increased developmental instability in this malocclusion due to high levels of genetic and environmental stress during the period of early development.